Caracterización zoométrica de caballos criollos en la parroquia boyacá, cantón Chone, provincia de manabí - Morales Moreira, Johann Saniago (2017)
ABSTRACT In parish Boyaca was the characterization of equine Creoles where through infinite population statistical formula, used 140 horses over 4 years of age, by means of descriptive statistics, it was determined the following measures zoometric: 23 head, width 34 cm (±1, 55), long head 55, 99 cm (±3, 44), width of 46, 24 cm rump (±3, 13), 45, 55 cm long (±2, 60) boosted the cross 140, 10 cm (±5, 05) boosted the rump 139, 38cm (±5, 34), longitudinal diameter 145, 45 cm (7, 57), bicostal 34, 32 cm diameter (±3, 46), sternal back 65. 2 cm (±3, 80), thoracic perimeter 152, 58 cm (±6, 65), perimeter of Reed 17, 84 cm (±1, 01), sacral hip height shows difference an ischio-iliac profile inclined 99,29%. For the calculated indices zoometric through frequencies, classified these animals as: dolichocephalic, curves, dolicotoraxico, dolicomorfo, correlation media between your body mass and thickness of their forelimbs, mesopelvico, of proportionality long, with straight face profile; cervical pyramidal, lumbar and ventral back normal. The layers most often were: chestnut (22,14%) followed by the layer chestnut (20%), presenting the most four black helmets (60,71%). It is concluded that these animals have the features zoometric and morphological similar to horses in the sierra.